SOME CASES OF CONSTRUCTING BICYCLIC T-FACTORIZATION OF GRAPHS Kn, n=4l+2, l≥1 BY THE METHOD OF PARALLEL TRANSFER OF INTERLOBAL EDGE - Мироненко, Оксана (SWorldJournal, 2025)
The work is devoted to the bicyclic T-factorization of the complete graph Kn, where n = 4l+2 and l≥1, and to the algorithm and method of parallel interlobular edge transfer when constructing such basic components of the bicyclic T-factorization. It has b